2018
DOI: 10.18683/germs.2018.1143
|View full text |Cite
|
Sign up to set email alerts
|

Soil contamination by Toxocara canis and human seroprevalence in the Attica region, Greece

Abstract: Background Toxocara canis is one of the most widespread public health and economically important zoonotic parasitic infections humans share with canids, mainly dogs. Human infection occurs by the accidental ingestion of embryonated eggs or larvae from a range of wild and domestic paratenic hosts. The aim of the present study was to examine the soil contamination of public places by the parasitic ova and to estimate serologically the prevalence of T. canis human infection in the Attica region, Greece. Methods I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 21 publications
3
19
0
Order By: Relevance
“…In Asia, the seroprevalence of toxocariasis was substantially high: 46.0% in Taiwan [12], 45.9% in Turkey [13], 49% in the Philippines [14], 51.2% in Korea, and 23.5-45.9% in Iran [15,16]. In Western countries, the prevalence was 5.0% in the USA [17], 8.0% in Italy [18], and 16.0% in Greece [19]. A systematic review and meta-analysis revealed that the global seroprevalence of toxocariasis was 19.0%, with the highest rate in the African region (37.7%) and the lowest rate in the Eastern Mediterranean region (8.2%) [20].…”
Section: Introductionmentioning
confidence: 99%
“…In Asia, the seroprevalence of toxocariasis was substantially high: 46.0% in Taiwan [12], 45.9% in Turkey [13], 49% in the Philippines [14], 51.2% in Korea, and 23.5-45.9% in Iran [15,16]. In Western countries, the prevalence was 5.0% in the USA [17], 8.0% in Italy [18], and 16.0% in Greece [19]. A systematic review and meta-analysis revealed that the global seroprevalence of toxocariasis was 19.0%, with the highest rate in the African region (37.7%) and the lowest rate in the Eastern Mediterranean region (8.2%) [20].…”
Section: Introductionmentioning
confidence: 99%
“…The results of this study agree with the data about soil contamination with T. canis eggs obtained by the authors from the Czech Republic 5.0 to 20.4 % (Dubná et al, 2007), Croatia -15.5 do 23.3 % (Stojčević et al, 2010), Spain -16.4 % (Dado et al, 2012), Poland -16.6 % (Bojar & Káapeü, 2012), Romania -17.17 % (Tudor, 2015) and Greece -17.2 % (Papavasilopoulos et al, 2018).…”
Section: Discussionmentioning
confidence: 97%
“…Similar rates were established among T. canis seropositivity and soil contamination within the same geographical areas. The proportion of seropositive samples in the group of children was significantly higher compared to the proportion of adults (48% versus 8%, p < 0.001) [ 21 ]. In Crete, Greece, totals of 879 dog and 264 cat fecal samples were examined in 2017.…”
Section: Introductionmentioning
confidence: 99%